Potency and developmental strategy of dairy cattle bussines in Pangkalan Kerinci, Pelalawan district - Septina Elida (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2016)
otential dairy development enhanced by availability of food, farmers knowledge, the demand for milk, farmer's income, market infrastructure, the role of credit institutions and government policies. The study aims are to analyze the condition of the resource, technical and economic aspects in the business of dairy cattle as well as alternative strategies for deployment. Research conducted using survey method. The results showed that the relative resource support dairy cattle business, family’s labor and the motivation to develop, fodder and traditional medicines obtained in the environment of the area, population LQ categorized as a regional base. Technical in dairy cattle business well known and economically advantageous RCR value of 2.22; GMP 56%; NPM 52%; TAT 48%; and the ROI of 11%. Based on the SWOT strategy in developing the dairy cattle business in the District of Pangkalan Kerinci is SO strategy (Strength-Opportunity), which is a strategy that supports an aggressive growth (Growth oriented), using enforcement utilization of opportunities and policy based on priorities. The development policies stategy consisting improving capital acces, maximized culture technology, increasing cattle population and production, improving farmer knowledge in diversification of agroindustri product, creating adequate forage, improving product competitiveness, and product promotion.